International Islamic University Malaysia: an assessment of 35 years of unique experience in Islamization of knowledge - Ahmad, Nadzrah; Akhmetova, Elmira; Ishak, Mohd Haeqal; Ahmad Nabil, Amir (2017)
International Islamic University of Malaysia (IIUM) is globally recognized for its commitment in spreading the spirit of Islamization of Knowledge (IOK). It implements various Islamization programs under premier IOK scholars. This study aims to discover the IOK experience of IIUM and broaden the understanding of the concept of Islamization in general. Works pertaining to IOK and its achievements in IIUM are discussed by focusing more on the strategies and impacts of IOK on IIUM‘s Mission and Vision. The result indicates that IIUM has achieved notable successes in its implementation of IOK over the 35 years of its establishment. IOK has not only contributed to the overall constitution of IIUM but also instilled an in-depth understanding of the Islamic spirit of education.